2006
DOI: 10.2741/1853
|View full text |Cite
|
Sign up to set email alerts
|

Chronically increased intrarenal angiotensin II causes nephropathy in an animal model of type 2 diabetes

Abstract: Diabetic nephropathy characterized by proteinuria and sclerosis is the leading cause of renal failure, but its mechanisms are not well understood. Zucker Obese (ZO) rat model of obesity, insulin resistance, and hypertension has been used to study nephropathy. We hypothesize that chronically elevated intrarenal angiotensin II (ANG II) down-regulates nephrin, a key slit-pore protein and up-regulates fibrogenic molecule transforming growth factor (TGFbeta1) and thus result in progression of nephropathy in type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
2
36
2
Order By: Relevance
“…This action of ANG II is way to be mediated chiefly with transforming growth factor-beta, which stimulates the synthesis and decreases the degradation of extracellular matrix components, as well as collagen types and fibronectin. 31 In our study, in diabetic rats (without treatment), volume of glomerular area, glomerulosclerosis, fibronectin and i-NOS expression were increased significantly when compared to control group (Group 1). However, a statistically meaningful reduction was determined in glomerulus area in diabetic rat group receiving enalapril and TMZ when compared to control rat group in our study.…”
Section: Discussionsupporting
confidence: 47%
“…This action of ANG II is way to be mediated chiefly with transforming growth factor-beta, which stimulates the synthesis and decreases the degradation of extracellular matrix components, as well as collagen types and fibronectin. 31 In our study, in diabetic rats (without treatment), volume of glomerular area, glomerulosclerosis, fibronectin and i-NOS expression were increased significantly when compared to control group (Group 1). However, a statistically meaningful reduction was determined in glomerulus area in diabetic rat group receiving enalapril and TMZ when compared to control rat group in our study.…”
Section: Discussionsupporting
confidence: 47%
“…The increases in ROS formation and urine isoprostanes in the ZO rat, independent of elevations in SBP, further suggest an association between insulin resistance/hyperinsulinemia, oxidative stress, and filtration barrier injury. There is accumulating data supporting the notion that the podocyte is susceptible to immunologic and inflammatory injury from ROS generated by endothelial cells [3, 4,35,36,37]. One proposed mechanism is that insulin resistance and the compensatory hyperinsulinemia may lead to enhanced oxidative stress and inflammation in the glomerulus with resultant downregulation of nephrin, an important protein necessary for maintenance of the slit pore diaphragm of the podocyte [35,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that diabetic increases in systemic and renal levels of ANG II and TGF-␤1 play critical roles in diabetic renal pathogenesis (3,28). Other studies also demonstrated the increase in UII levels along with ANG II and TGF-␤1 in the subjects with various pathogeneses (3,6,15,36,37).…”
Section: Diabetic Increases In Uii and Gpr14 Expressions Were Accompamentioning
confidence: 95%